Density of heterogeneous and homogeneous crystal nuclei in poly (butylene terephthalate). (May 2015) - Androsch, René; Rhoades, Alicyn Marie; Stolte, Isabell; Schick, Christoph
Graphical abstract: Highlights: The density of homogeneous nuclei is 10 15 nuclei per mm 3 There is observed a bimodal temperature-dependence of the crystallization rate. There is no change of the crystal polymorph on crystallization at different temperature. At high and low supercooling are observed nodules and lamellae, respectively. Abstract: Quantitative analysis of the nucleation density of poly (butylene terephthalate) using microscopy yielded values of 10 6 and 10 15 nuclei mm −3 for the cases of heterogeneous and homogenous nucleation on crystallization at low and high supercooling of the melt, respectively. Fast scanning chip calorimetry revealed that the largely different nucleation densities cause two crystallization-rate maxima at 130 and 70 °C, with characteristic minimum crystallization times of the high- and low-temperature crystallization processes being about 1 and 0.1 s, respectively. It has furthermore been excluded by X-ray scattering that the low-temperature crystallization-rate maximum is due to the formation of a different crystal polymorph; independent of the supercooling there is observed formation of α-crystals. The crystallization study has been completed by analysis of the non-isothermal crystallization behavior, identifying a minimum critical cooling rate of about 10 K s −1 to avoid completion of the high-temperature crystallization process and to initiate crystallization at low temperature. For complete vitrification, the PBT melt needs to be cooled faster than 200 K s −1 .